NextGen network synchronization - Chowdhury, Dhiman Deb (Springer, 2021)
This book presents time synchronization and its essential role as a conduit of optimized networks and as one of the key imperatives of ubiquitous connectivity. The author discusses how, without proper time synchronization, many mission critical infrastructures such as 5G mobile networks, smart grids, data centres CATV, and industrial networks would render in serious performance issues and may be subject to catastrophic failure. The book provides a thorough understanding of time synchronization from fundamental concepts to the application of time synchronization in NextGen mission critical infrastructure. Readers will find information not only on designing the optimized products for mission critical infrastructure but also on building NextGen mission critical infrastructure. Presents time synchronization and its importance in modern smart network infrastructure; Addresses sync plane issues of 5G mobile network infrastructure and designing optimized edge cloud and telecom cloud infrastructure; Discusses building optimized transport systems for smart grid, data centres CATV, and industrial network infrastructure.